2006
DOI: 10.1103/physrevb.73.115431
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of surface chemical reactions using a neural network representation of the potential-energy surface

Abstract: A neural network ͑NN͒ approach is proposed for the representation of six-dimensional ab initio potentialenergy surfaces ͑PES͒ for the dissociation of a diatomic molecule at surfaces. We report tests of NN representations that are fitted to six-dimensional analytical PESs for H 2 dissociation on the clean and the sulfur covered Pd͑100͒ surfaces. For the present study we use high-dimensional analytical PESs as the basis for the NN training, as this enables us to investigate the influence of phase space sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
121
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(121 citation statements)
references
References 72 publications
0
121
0
Order By: Relevance
“…Such an interpolation of high-dimensional PESs is a tedious task, but in recent years, several techniques, like analytical fits 29,31,32,33,34 , tight binding representations 35,36,37,38 , genetic programming 39 and the modified Shephard method 40,41 , possibly combined with a corrugation-reduction scheme 42,43 , have been developed. In the present work we employ a very general neural network fitting scheme, which has already proven to be a powerful tool for the accurate representation of multi-dimensional PESs in similar applications 44,45,46,47 . Since the evaluation of the energy and forces from the neural network representation is about 5 to 6 orders of magnitude faster than direct ab initio calculations, a large number of MD trajectories can be calculated in the last step of the "divide and conquer" approach to obtain the sticking probabilities at various molecular kinetic energies.…”
Section: Methodology a Calculation Of The Sticking Curvesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an interpolation of high-dimensional PESs is a tedious task, but in recent years, several techniques, like analytical fits 29,31,32,33,34 , tight binding representations 35,36,37,38 , genetic programming 39 and the modified Shephard method 40,41 , possibly combined with a corrugation-reduction scheme 42,43 , have been developed. In the present work we employ a very general neural network fitting scheme, which has already proven to be a powerful tool for the accurate representation of multi-dimensional PESs in similar applications 44,45,46,47 . Since the evaluation of the energy and forces from the neural network representation is about 5 to 6 orders of magnitude faster than direct ab initio calculations, a large number of MD trajectories can be calculated in the last step of the "divide and conquer" approach to obtain the sticking probabilities at various molecular kinetic energies.…”
Section: Methodology a Calculation Of The Sticking Curvesmentioning
confidence: 99%
“…70 In particular multilayer feedforward neural networks have already successfully been employed to provide accurate fits of potential-energy surfaces 44,45,46,47 . In the present work this NN type is applied to fit a smooth and continuous function to the DFT data by optimizing a set of parameters.…”
Section: Neural Network Interpolationmentioning
confidence: 99%
“…Previously proposed strategies include running molecular dynamics (MD), creating regular meshes of crystal structure parameters, selecting specific desired geometries, etc. [62][63][64]. The MD-based approach has the advantage of sampling commonly accessible physical states.…”
Section: Generation Of Training Datasetsmentioning
confidence: 99%
“…To use an alternative potential energy, Sumpter and Noid first systemically showed that neural networks are able to map the vibrational motion determined from spectra onto a fully coupled potential energy surface (PES) with a high accuracy [87]. Subsequently, people started to use ANN and other machine learning techniques for mapping the PES of some simple chemical reactions (e.g., H2 dissociation [88]) and molecular interactions (e.g., water dimer [89]). In terms of the global optimization of catalytic systems, Ouyang et al used an ANN with 56 independent variables in the input layer to fit the PES of Au58 clusters [90].…”
Section: Prediction Of Potential Energy Surfacementioning
confidence: 99%